Analisis Dampak Implementasi PSAK 73 Bagi Lessee dan Lessor - Gamalasari, Dinny; Wardhani, Nurhastuty Kesumo (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to analyze the impact of implementing PSAK 73 for lessee and lessors in companies in Indonesia. This research focus on the impact of implementing PSAK 73 in terms of financial performance and tax aspects in the mining sector (lessee) and the property & real estate sector (lessor). This research uses a qualitative approach with content analysis. The research data comprises audited financial reports obtained from the Indonesian Stock Exchange for the years 2018 to 2022. The results of this this study shows that there are differences in recording from the lessee side by recording the right of use assets and lease liabilities for the leased assets while the lessor side still continues the accounting standards that have been applied before. The application of PSAK 73 in the mining sector and the property and real estate sector does not have a significant impact on the company's financial statements. The company's financial performance and recording differences between accounting and tax are influenced by other factors. In addition, the results of this study indicate that companies need to mitigate the risks associated with changes in applicable accounting standards. This research provides a better understanding of how companies challenges of implementing this new standard and show it affects stakeholders, such as investors, financial analysts, and regulators. It is hoped that the results of this research will provide insight into the context of changes in accounting standards in Indonesia and provide a basis for further discussion about more transparent and relevant financial reporting.